Webquest Sebagai Pembelajaran Dimasa Pandemi Covid-19 Pada Mata Pelajaran Sejarah Indonesia Kelas X Di Smk Nurul Huda Poncokusumo Kabupaten Malang - Armedo Futhi Munadzar; Achmad Darojat (Jurnal Informatika dan Komputer, 2024)
The pandemic disease outbreak due to corona virus disease (Covid-19) has affected learning activities at both elementary and tertiary levels. The government requires students to carry out online learning activities. One online learning alternative that can be implemented is WebQuest. WebQuest is a type of web-based learning that is inquiry-oriented. In developing this WebQuest, the model used is Web-Based Instructional Design with four stages: 1) Analysis Stage, 2) Concurrent Design Stage, 3) Implementation Stage, 4) Evaluation Stage. This research was applied to 40 students of class Results of WebQuest trials with 3 experts. The results of data analysis from design experts obtained an average percentage of 80% suitable for use. The results of media expert data analysis obtained an average percentage of 90% suitable for use. The results of material expert data analysis obtained an average percentage of 88% suitable for use. The results of individual data analysis obtained an average percentage of 86.6% suitable for use. The results of small group data analysis obtained an average percentage of 85.7% suitable for use. The results of field test data analysis obtained an average percentage of 83.1% suitable for use. The number of students who fulfill the SKM reaches a percentage level of 87.5%, so the product is said to be effective. Meanwhile, in individual trials, small groups and field trials, it can be concluded that the WebQuest that has been developed is valid and suitable for use in learning activities. Learning with WebQuest can be the main alternative for online learning during the Covid-19 pandemic. WebQuest makes it easy for students to access study material by simply opening one website page. Apart from the material in WebQuest, there are also assignments/activities that can attract students to learn using WebQuest.Keyword: WebQuest, Study activity in the time of Covid-19 Pandemic, Indonesian History.